Aberrant motor contagion of emotions in psychopathy and high-functioning autism - Sun Lihua; Lukkarinen Lasse; Noppari Tuomo; Nazari-Farsani Sanaz; Putkinen Vesa; Seppälä Kerttu; Hudson Matthew; Tani Pekka; Lindberg Nina; Karlsson Henry K.; Hirvonen Jussi; Salomaa Marja; et al. (OXFORD UNIV PRESS INC, 2022)
Psychopathy and autism are both associated with aberrant social skills and empathy, yet only psychopaths are markedly antisocial and violent. Here, we compared the functional neural alterations underlying these two groups that both have aberrant empathetic abilities but distinct behavioral phenotypes. We studied 19 incarcerated male offenders with high psychopathic traits, 20 males with high-functioning autism, and 19 age-matched healthy controls. All groups underwent functional magnetic resonance imaging while they viewed dynamic happy, angry, and disgusted faces or listened to laughter and crying sounds. Psychopathy was associated with reduced somatomotor responses to almost all expressions, while participants with autism demonstrated less marked and emotion-specific alterations in the somatomotor area. These data suggest that psychopathy and autism involve both common and distinct functional alterations in the brain networks involved in the socioemotional processing. The alterations are more profound in psychopathy, possibly reflecting the more severely disturbed socioemotional brain networks in this population.